2021
DOI: 10.1002/icd.2241
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood education and care (ECEC) during COVID‐19 boosts growth in language and executive function

Abstract: High‐quality, centre‐based education and care during the early years benefit cognitive development, especially in children from disadvantaged backgrounds. During the COVID‐19 pandemic and its associated lockdowns, access to early childhood education and care (ECEC) was disrupted. We investigate how this period affected the developmental advantages typically offered by ECEC. Using parent‐report data from 189 families living in the UK, we explore associations between time spent in ECEC by 8‐to‐36‐month‐olds, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 51 publications
3
42
0
2
Order By: Relevance
“…A recent study has observed that children born and raised during COVID-19 have a lower score on overall cognitive development than the infants' born and raised before the pandemic (Deoni et al, 2021 ). Another study suggested that attending nursery in contrast to staying at home during the pandemic correlated with better language outcomes (Davies et al, 2021 ). However, even though we observed lower scores on communicative development in the current data, we did not observe a clear relation between the CSBS and segmentation abilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has observed that children born and raised during COVID-19 have a lower score on overall cognitive development than the infants' born and raised before the pandemic (Deoni et al, 2021 ). Another study suggested that attending nursery in contrast to staying at home during the pandemic correlated with better language outcomes (Davies et al, 2021 ). However, even though we observed lower scores on communicative development in the current data, we did not observe a clear relation between the CSBS and segmentation abilities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a UK study analyzed language learning in 8–36-month-old infants growing up during the pandemic. The authors compared those infants that continued attending nursery with those that stayed at home and concluded that infants from a lower socioeconomic background had their receptive vocabulary growth boosted if attended nursery (Davies et al, 2021 ). The study suggested that activities in the nursery are especially beneficial for those infants that are coming from a more challenging background.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, of course, was not true for all American families. Emerging research on the impacts of COVID-related ECEC closures in the UK suggests that loss vs. maintenance of outside-the-home care was more strongly correlated with the language development outcomes of young children from less economically advantaged homes with fewer resources to compensate (Davies et al, 2021). In the current study, families who were facing major health, financial, and childcare crises were not represented, and would not have been likely to prioritize taking the time to complete this voluntary shared reading survey.…”
Section: Discussionmentioning
confidence: 99%
“…We know from two very recent studies of the impacts of COVID-19 lockdowns that changes in care routines appear to have had a general impact on younger children's language development. Davies et al (2021) found that with a sample of 189 families living in the UK, there was a positive association for 8-to 36-month-old children in the amount of time they spent in ECEC and their language growth from Spring to Winter 2020, such that receptive vocabulary growth was stronger for toddlers who were able to continue attending ECEC during the period. In another recent study of 1742 children across 13 countries, Kartushina et al (2021) found that 8-to 36-month-old toddlers who spent more time during the initial COVID-19 lockdowns (from March to September of 2020) participating in shared reading with their in-home caregivers, as well as children who engaged less in passive screen viewing, had larger increases in their expressive vocabulary size.…”
mentioning
confidence: 95%